2021
DOI: 10.23887/jisd.v5i4.39770
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning and Character Building in Rural Area During the Covid-19 Pandemic

Abstract: The COVID-19 pandemic has brought a number of obstacles and challenges in learning. The bigger obstacle is found for schools in rural areas. Starting from the problem of the availability of supporting facilities, parental support, to the problem of teacher readiness in carrying out learning and character education during the COVID-19 pandemic. Therefore this study aims to describe the teacher's strategy in carrying out distance learning and character education in rural area during the Covid-19 pandemic. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…There needs to be government and stakeholder intervention to ensure the improvement of the online learning infrastructure (Adiyarta et al, 2018;Ekalestari et al, 2021). Besides being able to provide standardized home-based learning/teaching tools to educators and students, as well as increasing teacher capacity through online teacher training (Dewantara & Dibia, 2021;UNICEF, 2021;Zafar, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There needs to be government and stakeholder intervention to ensure the improvement of the online learning infrastructure (Adiyarta et al, 2018;Ekalestari et al, 2021). Besides being able to provide standardized home-based learning/teaching tools to educators and students, as well as increasing teacher capacity through online teacher training (Dewantara & Dibia, 2021;UNICEF, 2021;Zafar, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate research has identified various benefits from implementing e-learning, yet it does not stand that all institutions that implement online learning get the results as expected (A. Y. Alqahtani & Rajkhan, 2020;Dewantara & Dibia, 2021;Wu et al, 2021). Some organizations are not ready to implement e-learning because they experience challenges in technology, organization, culture, lesson design, and challenges by teachers and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four-minute policy decision in 2020, including the Minister of Education and Culture, stated that the principles of education policy during COVID-19 prioritize the health and safety of all parties involved in the learning process in schools and madrasahs. For this reason, a learning method is needed to accommodate this so that the learning process can run to educate the nation's children (Dewantara and Dibia, 2021).…”
Section: The Implementation Of Character Education Through Distance L...mentioning
confidence: 99%
“…Due to the pandemic situation caused by Covid-19, the online learning process massively conducted in education (Dewantara & Dibia, 2021;Iswahyudi, 2021;Saha et al, 2021). The common alternative way for educators to teach and share pre-service English teachers' learning materials is through a webinar session by utilizing electronic devices and internet connections.…”
Section: Introductionmentioning
confidence: 99%